A Insuficiência Cardíaca Crônica: o que dizem as diretrizes brasileiras - Carolina Teófilo Leite; Karla Gabrielly Barros de Jesus Sousa; Pedro Henrique MouraTeixeira; Júlio Alexandre Gemente Lozano; Denise Nogueira Chaves; Andressa Moreira Braz; Daniel Ruiz Agum; Maria Clara Diniz Martins; Elane Santos da Silva; Ailton Da Silva Ribeiro; Bernardo Andrade de Queirós; Bernardo Humberto Michiles Vianez; et al. (Brazilian Journal of Implantology and Health Sciences, 2024)
Device innovations over the past few decades have provided improvements in the diagnosis and treatment of patients with heart failure. These new tools were progressively adapted to minimally invasive strategies and percutaneous options multiplied rapidly. In this article we review the current and future directions of devices used as adjuvant options for the diagnosis and adjuvant treatment of chronic heart failure, their development, mechanisms and more recent studies.